PTH-137 Endoscopy experience for UK trainees in khartoum, sudan: south yorkshire experience. (8th June 2018) - Min, Thazin; Al-Rifaie, Ammar; Smith, Karen; Hurlstone, Paul; Abdo, Abdelmounem; Said, Elmuhtady; Donnelly, Mark
Abstract : Introduction: There is increasing interaction between UK gastroenterologists and those in resource-challenged countries. Our group has established links over 7 years with the Sudanese Society of Gastroenterology (SSG) and have previously provided training and support for consultant trainers, trainee endoscopists and endoscopy nurses, as well as supporting the annual SSG conference. Our host hospital, Ibn Sina (IS) is the national gastrointestinal centre and a World Gastroenterology Organisation training centre. Up to 60 cases of oesophageal varices are admitted per week. This is accounted for by the endemic nature of schistosomiasis and a high prevalence of viral hepatitis. This year, we arranged for 2 UK StRs to travel to Sudan to experience therapy for bleeding varices and to work in a resource-limited environment. Methods: Two ST4 registrars were selected from the South Yorkshire region after a competitive application process. Funding was provided by UK based Sudanese doctors, SSG and local research funds. They performed UGI endoscopy from 8th – 11th of January 2018 at IS. The trainees were JAG accredited for diagnostic gastroscopy (OGD) only, therefore all therapeutic interventions were supervised. Prior experience of one registrar was 370 OGDs with 4 variceal band ligation – VBL (16 months). Registrar 2 had performed 242 OGDs, one VBL (24 months). All patients provided written consent. Pharyngeal anaesthesia and/or intravenous sedation are not routinely used. Prospective collection of data included demographics, indications, endoscopic diagnosis and therapy. Results: Between the 2 UK StRs, 29 OGDs were performed in 4 days. These were both acute (14) and elective therapeutic (15) cases with a mean age of 51. 16 patients had VBL; 5 patients had sclerotherapy because of the unavailability of VBL; 1 patient had histoacryl glue injection of gastric varices; 1 had an oesophageal balloon dilatation. 6 patients did not require interventions. 55% (16/29) were related to periportal fibrosis; 14% (4/29) were related to hepatitis cirrhosis. Table 1: UGI endoscopic therapeutics performed over 4 days Conclusion: There is increasing cooperation between UK endoscopy and resource poor countries focusing on endoscopic training and support of their services. We have demonstrated that UK trainees can also benefit hugely from such interactions, both in terms of exposure to and skills acquisition from dealing with clinical problems relatively rare in UK training as well as experiencing the challenges of working in a resource poor healthcare setting. We would encourage these interactions as a mutually beneficial partnership. We plan to make the participation of our StRs a regular feature of our collaboration with SSG.